Transient Neurologic Symptoms following Spinal Anesthesia with Isobaric Mepivacaine: A Decade of Experience at Toronto Western Hospital - Ashwin Sankar; Minou Behboudi; Faraj W. Abdallah; Alan Macfarlane; Richard Brull (Anesthesiology Research and Practice)
Background. Transient neurologic symptoms (TNSs) can be distressing for patients and providers following uneventful spinal anesthesia. Spinal mepivacaine may be less commonly associated with TNS than lidocaine; however, reported rates of TNS with intrathecal mepivacaine vary considerably. Materials and Methods. We conducted a retrospective cohort study reviewing the internal medical records of surgical patients who underwent mepivacaine spinal anesthesia at Toronto Western Hospital over the last decade to determine the rate of TNS. We defined TNS as new onset back pain that radiated to the buttocks or legs bilaterally. Results. We found one documented occurrence of TNS among a total of 679 mepivacaine spinal anesthetics (0.14%; CI: 0.02–1.04%) that were performed in 654 patients. Conclusion. Our retrospective data suggest that the rate of TNS associated with mepivacaine spinal anesthesia is lower than that previously reported in the literature.